Influence of Workload and Compensation on Job Satisfaction in the Accommodation Service Sector with Work Life Balance as Moderating Effect - Rolan Adhytia Lando; Hendra Lukito; Harif Amali Rivai (Enrichment : Journal of Management, 2023)
Job satisfaction in every company has a different level. This research tries to test job satisfaction with compensation and workload as independent variables at Pangeran Beach Hotel Padang as an accommodation company in the service sector. Using work life balance as moderator, this study distributed questionnaires to 64 out of 125 employees who had been screened using a purposive sampling technique. The results of the data obtained were processed by descriptive analysis using SmartPLS 3.0 and it was found that workload had a negative and significant effect on job satisfaction, compensation and work life balance had no effect on job satisfaction, and work life balance moderated the relationship between workload and compensation on job satisfaction. In this research, there is 32.8% of value where job satisfaction can be influenced by other variables and not explained and can be given number of respondents or variable variations as an alternative for limitations.